Wish - O'Connor, Barbara (New York Scholastic, 2017)
"A story about a girl who, with the help of the dog of her dreams, discovers that family doesn't always have to be related--they are simply people who love you for who you are"--Provided by publisher.
850
T
Accelerated Reader
Keywords: Human-animal relationships -- Fiction; Dogs -- Fiction; Family life -- Fiction; Conduct of life -- Fiction